Talent management practices on employee engagement : empirical perspective from institution of higher learning - Mohammed Sani Abdullahi; Adams Adeiza; Umair Ahmed; Nadeem Khalid; Gwadabe, Zainab Lawan; Fawehinmi, Olawole (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of this research is to investigate the effect of talent management (TM) practices on employee engagement (EE) in Malaysia Private Universities (MPU). The present research applied a cross-sectional research approach, and the study data were collected from 314 academics from MPU. Partial Least Square-Structural Equation Modelling (PLS-SEM) was employed to evaluate the study hypotheses. The findings showed that TM practices: talent recruitment practice (TRP), training and development practice (T&DP), and compensation practice (CP) has a significant effect on EE. This research is one of its kind conducted in MPU. Therefore, this research makes significant contributions to the existing literature by investigating the effect of TRP, T&DP, CP on EE, and also the findings of the research serve as a guide to the universities management to formulate their institutional policies to inspire their employees to engage in their task effectively which can enable the universities to fulfil their specified mission and vision.